2012
DOI: 10.1039/c2cp42448g
|View full text |Cite
|
Sign up to set email alerts
|

Direct correlation between work function of indium-tin-oxide electrodes and solar cell performance influenced by ultraviolet irradiation and air exposure

Abstract: We report on reversible changes of the work function (WF) values of indium-tin-oxide (ITO) under prolonged ultraviolet (UV) and air exposure. The WF of ITO is reduced from 4.7 eV to 4.2 eV by photon absorption in ITO under UV illumination or an air mass 1.5 solar simulator (100 mW cm(-2)). Air or oxygen exposure is found to increase the WF of ITO (UV-exposed) to a value of 4.6 eV. These changes of ITO's WF lead to reversible variations of the performance of organic photovoltaic devices where ITO acts primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 36 publications
7
72
0
1
Order By: Relevance
“…Zhou et al proposed that the adsorbed oxygen can strongly influence the WF of ITO, and the oxygen can be deposited after UV irradiation, resulting in lower WF of ITO,37 which is in line with the LS effect of i‐PSCs with ITO/EC interlayer electrodes. We experimentally confirm that the origin of the LS effect of ITO/EC interlayer comes from the variation of the Fermi levels due to the presence of dipoles formed after O 2 adsorption which have an opposite direction to the dipole induced by the EC interlayer.…”
Section: Resultsmentioning
confidence: 75%
“…Zhou et al proposed that the adsorbed oxygen can strongly influence the WF of ITO, and the oxygen can be deposited after UV irradiation, resulting in lower WF of ITO,37 which is in line with the LS effect of i‐PSCs with ITO/EC interlayer electrodes. We experimentally confirm that the origin of the LS effect of ITO/EC interlayer comes from the variation of the Fermi levels due to the presence of dipoles formed after O 2 adsorption which have an opposite direction to the dipole induced by the EC interlayer.…”
Section: Resultsmentioning
confidence: 75%
“…The currentvoltage (I-V) measurements were conducted by Keithley 2400 with 100 mW/cm 2 (AM 1.5G) simulated sunlight from a Newport solar simulator. To avoid the work function variation of ITO under exposure to the simulated sunlight [41], the devices were kept in dark after the measurements under short illumination (no light soaking) in glove box. The EQE of the devices was calculated from the photocurrent measured by a lock-in amplifier.…”
Section: Characterization Of Inverted Pscs and Thin Filmsmentioning
confidence: 99%
“…cathode interfacial layer materialsIn the past few years, the potential of other catalog cathode interfacial materials has been extensively investigated, and some of them have been demonstrated as promising candidate for PSCs in all kinds of device configurations. For example, in 2012 Zhou et al[50,51] demonstrated that a thin layer of nonconjugated polyelectrolyte, polyethylenimine ethoxylated (PEIE) and branched polyethylenimine (PEI), could be utilized as a cathode surface modifier to produce low work function contact for organic electronic devices, mainly due to the intrinsic dipole moments of the polymers and the electron transfer between ethylamine and the electrode. When utilizing P3HT:ICBA as the photoactive layer, the resulted inverted PSCs from ITO/PEIE, Ag/PEIE and PH1000/ PEIE substrates showed PCEs of 5.9%, 2.6% and 3.5%, respectively, demonstrating that nonconjugated polyelectrolyte can be general surface/interfacial materials for high-efficiency PSCs.…”
mentioning
confidence: 99%